The study of e-book usage in teaching and learning: Primary and secondary school - Zainal Abidan, Meor Ahmad Shukri; Aziz, Fakhrul Anuar (2006)
Electronic book is designed to store and display reading material particularly in learning environment. The introduction of e-book into classroom teaching has been involved for years, but the technology has never stop been up to the task.This article will describe the study of e-book usage in school teaching and the effectiveness of e-book usage based on student test and feedback. Student responses to the questionnaires showed that the e-book could interest them to the study by offering several advantages over printed texts. Comments from participants indicate that the prototype performed accordingly to their needs and expectation. Data will be presented on initial learning curve , advantages and disadvantages of electronic texts and student’s performance chart for using e-book application.